The structure of the development of voice culture of future teacher: Theoretical and methodological aspect - Lyudmyla Peretyaha, Lyudmyl (Professional Art Education, 2022)
The purpose of the article essence of the voice culture of the future teacher and reveals the structure, which is represented by the unity of four interconnected structural blocks: professional (pedagogical), technical, hygienic, psychological.Methods and methodology. The article used a set of methods typical for research of a similar level, namely: the descent from the abstract to the concrete, a systemic, structural-activity approach; method of scientific knowledge, comparison.The novelty lies in the holistic identification of functional components that ensure the implementation of the structural components of voice culture, and their selection reveals the procedural side of this issue.Results. It was established that voice culture has a complex structure, which is represented by the unity of four interrelated blocks: professional and pedagogical, which ensures the full disclosure of voice capabilities of representatives of pedagogical professions with a large voice load (teacher); technical unit, which forms a “technical base” for active vocal use and ensures preparation of the vocal apparatus for increased vocal load: hygienic unit, which maintains the vocal apparatus in a healthy and functional state; psychological block, which is aimed at achieving mutual understanding with others (subjects of the pedagogical process) by taking into account the peculiarities of voice formation. The selected structural blocks are represented by the unity of four universal components for each structural block: motivational-axiological, cognitive, activity-practical and reflective. The named components reflect the sequence of the structure of the vocal culture blocks we have selected. Based on the specificity of the teacher's activities and the variability of his relationships, the main functions are defined: cognitive, gnostic, value-oriented, prognostic-oriented, prognostic-prophylactic, communicative, developmental-educational, energetic, distributional, protective, reflexive-corrective.Conclusions. A teacher's mastery of voice culture allows reducing the negative impact of factors of professional activity on the state of the teacher’s vocal apparatus. At the same time, it allows you to maintain the state of the vocal apparatus in a healthy and functional state, through technical improvement through mastering effective techniques for its use depending on the tasks and conditions of professional activity. It can be assumed that the development of vocal culture helps to achieve better interaction with others and with minimal consequences for the condition of one's vocal apparatus.
Keywords: voice; speech voice; voice disorders; prospective teachers; voice culture; structural blocks; structural and functional components; professional training